Biotechnological applications of microalgae : biodiesel and value added products - Bux, F. (Faizal) (Boca Raton, Fla. : CRC Press, 2013)
"Preface Over the decades, much of the literature has focused on the biology and ecological aspects of algae found in freshwater, marine, and brackish environments. These organisms are also known to inhabit various other environments on Earth. More recently, there has been a substantial shift toward the concept of sustainable development and the "green economy" with emphasis on exploiting biological systems for the benefit of mankind. This underpins the fundamentals of the field of biotechnology, which has revolutionized various fields including agriculture, food, pharmaceutical and medical sciences, environmental sciences, and industrial feedstock, thus positively impacting most spheres of human endeavor. Algae--but more specifically, microalgae--have been associated with problematic events such as algal blooms caused by eutrophication of aquatic environments and in some cases the toxins produced have serious health impacts on the aquatic environment, plants, animals, and humans. However, these events are largely due to human activities resulting in the proliferation of nutrients in aquatic environments. The significance of algae cannot be underestimated as they contribute to approximately 40% of the oxygen in the atmosphere, are the original source of fossil fuels, and are the primary producers in the oceans. Therefore, there is potential for exploitation of this invaluable biomass source that could lead to definite environmental and economic benefits for man"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Microalgae -- Biotechnology; Biomass energy; Microalgae -- Industrial use; Electronic books